Representasi Maskulinitas Iklan Gudang Garam versi filter Internasional 2023 The Greatest Choice Pria Punya Selera - Mohamad Rizaldi Mughni (Brand Communication, 2023)
Abstract: This research is a qualitative research with communication semiotic methodology. The object of this research is the Gudang Garam cigarette advertisement in the YouTube media account. The analytical method used in this research is Charles Sanders Pierce's semiotic method. Based on the results of the analysis, the representation of masculinity in the Gudang Garam cigarette advertisement, the International 2023 filter version, is symbolized by an athletic body shape, tall and well-built body. The representation of a masculine male appearance is symbolized through a handsome face of olive skin with thick eyebrows and a thin mustache and beard. Supporting representations that symbolize masculinity in the filtered version of Gudang Garam cigarette advertisements International 2023 include: Clothing attributes worn such as shirts and suits, vehicle attributes symbolized by a collection of luxury cars, an attitude of innovation, a breakthrough idea, dare to take risks and process a challenge to career success in the future, as well as the attitude of responsibility as a masculine man.